Efek Ekstrak Dan Fraksi Daun Salung (Psychotria viridiflora Reinw. ex. Blume) Sebagai Sitotoksit, Antiproliferasi dan Penginduksi Apoptoksis pada Sel Kanker Serviks HeLa - Salni Salni; Arlina Ismaryani; Arum Setiawan; Triwani Triwani (JURNAL ILMU KEFARMASIAN INDONESIA, 2018)
Cervical cancer ranks second of cancer that affects women in the world and the first order for women in developing countries. Plant Salung (Psychotria viridiflora Reinw. Ex. Blume) have been used for generations to treat various diseases. The purpose of the study to determine the effects of leaf extracts and fractions salung as the anti-proliferation and inducer of apoptosis in HeLa cervical cancer cells. Concentration of extracts and fractions of 640; 320; 160; 80; 40 µg/mL, while cisplatin using a concentration of 200; 100; 50; 25 µg/mL. The results showed IC50 extract value 380.7 µg/mL. n-hexane fraction amounted to 229.3 µg/mL. ethyl acetate fraction of 116.8 µg/mL, and amounted to 562.8 µg/mL fraksi methanol water, so that the ethyl acetate fraction had enough categories active cytotoxic activity seen from the IC50. To further test the researchers only tested the active fraction is the fraction of ethyl acetate. Results ethyl acetate fraction doubling time is 58, which means replicating or proliferating cells on hour to 58 while the cells replicate cisplatin on the hour to 64.5 and the control cell on the hour to 41. Results of flowcytometry showed ethyl acetate fraction induce apoptosis by 72.82% while cisplatin 87.96%. It can be concluded that the extracts and fractions of leaves salung have a cytotoxic effect, acts as an anti-proliferation and inducer of apoptosis in HeLa cervical cancer cell.